First record and description of the female genitalia of Palingonalia subta Freytag & Vargas, 2007 (Hemiptera, Cicadellidae, Cicadellini) from Amazonas state, Brazil, and distribution map for the genus - Alexandre Cruz Domahovski; Luísa Alasmar; Rodney Ramino Cavichioli; Andrielli Oliveira; Sâmia Leticia Reolon da Cruz; Jefferson Marcelo Arantes-da-Silva; Nayane Silva de Oliveira; Torbjørn Haugaasen; Carlos A. Peres; Andressa Paladini (Check List, 2023)
Palingonalia Young, 1977 is a small, poorly known genus of Neotropical leafhoppers comprising only three described species. Here, we describe for the first time the female genitalia of Palingonalia and provided the first record of P. subta Freytag & Vargas, 2007 from Amazonas state, Brazil. Additionally, a distributional map for the genus, discussion about its distribution, and key to species are provided.